Comprehensive RNA-Seq Profiling Reveals Temporal and Tissue-Specific Changes in Gene Expression in Sprague–Dawley Rats as Response to Heat Stress Challenges - Dou, Jinhuan; Cánovas, Angela; Brito, Luiz F.; Yu, Ying; Schenkel, Flavio S.; Wang, Yachun (Frontiers in Genetics, 2021)
Understanding heat stress physiology and identifying reliable biomarkers is paramount for developing effective management and mitigation strategies. However, little is known about the molecular mechanisms underlying thermal tolerance in animals. In an experimental model of Sprague-Dawley rats subject to temperatures of 22 ± 1℃ (control group; CT), and 42℃ for 30 min (H30), 60 min (H60), and 120 min (H120), RNA-Sequencing (RNA-Seq) assays were performed for blood (CT and H120), liver (CT, H30, H60, and H120), and adrenal glands (CT, H30, H60, and H120). A total of 53, 1,310, and 1,501 differentially expressed genes (DEG) were significantly identified in the blood (P < 0.05 and |fold change (FC)| > 2), liver (P < 0.01, false discovery rate (FDR)-adjusted P value = 0.05 and |FC| > 2) and adrenal glands (P < 0.01, FDR-adjusted P value = 0.05 and |FC| > 2). Four DEG, namely Junb, P4ha1, Chordc1, and RT1-Bb were shared among the three tissues in CT vs. H120. Functional enrichment analyses of the DEG identified in the blood revealed 12 biological processes (BP) and 25 metabolic pathways significantly enriched (FDR = 0.05). In the liver, 133 BP and three metabolic pathways were significantly detected by comparing CT vs. H30, H60, and H120. Furthermore, 237 BP were significantly (FDR = 0.05) enriched in the adrenal glands and no shared metabolic pathways were detected among the different heat stressed groups of rats. Five and four expression patterns (P < 0.05) were uncovered by 73 and 91 shared DEG in the liver and adrenal glands, respectively, over the different comparisons. Among these, 69 and 73 genes, respectively, were proposed as candidates for regulating heat stress response in rats. Finally, together with genome-wide association study (GWAS) results in cattle and Phenome-wide association studies (PheWAS) analysis in humans, five genes (Slco1b2, Clu, Arntl, Fads1, and Npas2) were considered as being associated with heat stress response across mammal species. The datasets and findings of this study will contribute to a better understanding of heat stress response in mammals and to the development of effective approaches to mitigate heat stress response in livestock through breeding.